2014
DOI: 10.3389/fnhum.2014.00676
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the neural circuits underlying reaching and reach-to-grasp movements: from planning to execution

Abstract: Experimental evidence suggests the existence of a sophisticated brain circuit specifically dedicated to reach-to-grasp planning and execution, both in human and non-human primates (Castiello, 2005). Studies accomplished by means of neuroimaging techniques suggest the hypothesis of a dichotomy between a “reach-to-grasp” circuit, involving the anterior intraparietal area, the dorsal and ventral premotor cortices (PMd and PMv – Castiello and Begliomini, 2008; Filimon, 2010) and a “reaching” circuit involving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 97 publications
6
28
0
Order By: Relevance
“…Reaching‐only and reach‐to‐grasp actions could be better characterized by temporal, rather than spatial criteria across planning and execution stages of the action, as also suggested by a recent study of Begliomini et al. (2014). Here we showed that several areas of the human reaching–grasping network are involved in processing aspects related to both reach‐to‐grasp and reaching‐only actions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaching‐only and reach‐to‐grasp actions could be better characterized by temporal, rather than spatial criteria across planning and execution stages of the action, as also suggested by a recent study of Begliomini et al. (2014). Here we showed that several areas of the human reaching–grasping network are involved in processing aspects related to both reach‐to‐grasp and reaching‐only actions.…”
Section: Resultsmentioning
confidence: 99%
“…2014; Culham et al. 2006; Vesia and Crawford, 2012) and has been shown to be involved in the representation of both the transport and the hand preshaping components of reaching‐only and reach‐to‐grasp actions, respectively (e.g., Fabbri et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For feedback, the left M1 received influence from the fronto-parietal cortices, which are engaged in motor preparation and control [2830]. Impressively, the causal flow from the prefrontal cortex and the posterior parietal cortex disappeared in both the PPH and CPH groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regional factors (anterior-posterior & left-right) were also included; see below section 2.6). Action type (grasping vs. pointing) was not included because the two blocks do not constitute independent levels of one variable, e.g., [72,73,74]. Furthermore, grasping and pointing movement are not strictly comparable as they differ kinematically [75,59,76] and seem to rely on non-identical neural networks [31].…”
Section: Methodsmentioning
confidence: 99%